2001
DOI: 10.1073/pnas.131572798
|View full text |Cite
|
Sign up to set email alerts
|

Wheat leaves emit nitrous oxide during nitrate assimilation

Abstract: Nitrous oxide (N2O) is a key atmospheric greenhouse gas that contributes to global climatic change through radiative warming and depletion of stratospheric ozone. In this report, N2O flux was monitored simultaneously with photosynthetic CO2 and O2 exchanges from intact canopies of 12 wheat seedlings. The rates of N2O-N emitted ranged from <2 pmol⅐m ؊2 ⅐s ؊1 when NH 4 ؉ was the N source, to 25.6 ؎ 1.7 pmol⅐m ؊2 ⅐s ؊1 (mean ؎ SE, n ‫؍‬ 13) when the N source was shifted to NO 3 ؊ . Such fluxes are among the small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
127
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(138 citation statements)
references
References 38 publications
8
127
0
3
Order By: Relevance
“…We were only able to find four other publications that emphasize the role of N 2 O emissions from plants (Chang et al, 1998, Rusch and Rennenberg, 1998, Smart and Bloom, 2001, and Pihlatie et al, 2005a. Chang et al (1998) postulated that significant amounts of N 2 O may also be emitted via herbaceaous plant transpiration, but also found that watering the soil with an N 2 O rich solution immediately increases N 2 O emissions from the above-ground parts of the plant, which suggests that N 2 O is conveyed to the leaves via the transpiration stream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were only able to find four other publications that emphasize the role of N 2 O emissions from plants (Chang et al, 1998, Rusch and Rennenberg, 1998, Smart and Bloom, 2001, and Pihlatie et al, 2005a. Chang et al (1998) postulated that significant amounts of N 2 O may also be emitted via herbaceaous plant transpiration, but also found that watering the soil with an N 2 O rich solution immediately increases N 2 O emissions from the above-ground parts of the plant, which suggests that N 2 O is conveyed to the leaves via the transpiration stream.…”
Section: Discussionmentioning
confidence: 99%
“…Rusch and Rennenberg (1998) found similar conditions in trees. Smart and Bloom (2001) used 15 N labeled fertilizer to be able to more specifically find out where plant emitted N 2 O is actually produced. In contrast to the previous two studies they found that labeled NH + 4 fertilizer did not increase N 2 O emission significantly, whereas NO − 3 fertilizer did.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrous oxide (N 2 O) is one of the three major biogenic greenhouse gases contributing to global warming, produced primarily from denitrification processes in agricultural systems (5,7). Also, assimilation of NO 3 Ϫ by plants can result in further N 2 O emissions directly from plant canopies (8). The low agronomic N-use efficiency (NUE) found in many agricultural systems is largely the result of N losses associated with nitrification (i.e., N losses from NO 3 Ϫ leaching and denitrification) (9)(10)(11).…”
mentioning
confidence: 99%
“…1 , results in the direct emission of N 2 O from crop canopies, further reducing nitrogen use efficiency (NUE; Smart and Bloom, 2001). Thus, maintaining soil N in NH 4 1 form is advantageous even after taking into consideration the potential negative effects of rhizosphere acidification from its uptake and assimilation (caused by H 1 excretion).…”
mentioning
confidence: 99%